Determinan Kualitas Laporan Keuangan Badan Penanggulangan Bencana Daerah Provinsi NTB (Studi Kasus Pada BPBD Se-Provinsi Nusa Tenggara Barat) - Aminuddin; Pancawati, Rr. Sri (Fakultas Ekonomi dan Bisnis Unram, 2024)
This research aims to determine the determinants of the quality of financial reports of regional disaster management agencies in NTB province. Raised several issues including the implementation of SIA, SAP, quality of human resources, internal control, and organizational commitment whether they have an influence on the quality of the financial reports of the Regional Disaster Management Agency of NTB Province. The method used in sampling was non probability sampling with a saturated sample method. A total of 17 BPBD offices in NTB province were used in this research. The data used is questionnaire data by taking questionnaire data with the time period 2018-2022. The results of this research show that the SIA (X1), SAP (X2) and internal control (X4) variables have a positive and significant influence on the quality of the NTB Province BPBD financial reports. Meanwhile, the HR quality variables (X3) and (X5) have a positive but not significant influence on the quality of the NTB Province BPBD financial reports.